Exploring Adenylylation and Phosphocholination as Post‐Translational Modifications. Issue 1 (31st October 2013) - Müller, Matthias P.; Albers, Michael F.; Itzen, Aymelt; Hedberg, Christian
<x xml:space="preserve">Abstract</x> Editing the translations: Adenylylation and phosphocholination have recently been found as important post‐translational modifications used by pathogenic bacteria during the infection process. This review discusses the combined use of chemical handles and specific antibodies for the identification of previously unknown substrates of these post‐translational modifications in infected host cells.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>